2018
DOI: 10.1155/2018/7053839
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Postoperative Complications among the Elderly after Plastic Surgery Procedures Performed under General Anesthesia

Abstract: Background The frequency of surgery involving elderly patients has been increasing. The use of free tissue transfers in the elderly has been examined previously (Howard et al., 2005, Hwang et al., 2016, Grammatica et al., 2015, Serletti et al., 2000, and Sierakowski et al., 2017), whereas there have not been any such studies of plastic surgery procedures. We evaluated the risk factors for complications after plastic surgery procedures performed under general anesthesia in patients aged ≥75 years. Methods The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…Fukui et al has shown that the duration of operation has the strongest effect on the risk of complications in terms of both medical and surgical complications in elderly patients undergoing plastic surgery procedures. In addition, they reported that low serum albumin levels increased the frequency of complications, especially in patients with ulcers (pressure sores, PAD, necrotizing fasciitis, and diabetic ulcers), and they developed more frequent postoperative complications compared to other patients (19). In our study, it is seen that there was a significant relationship between the complication rates and the disease type, just as the correlation between the duration of surgical operation and ASA ps score.…”
Section: Discussionsupporting
confidence: 58%
“…Fukui et al has shown that the duration of operation has the strongest effect on the risk of complications in terms of both medical and surgical complications in elderly patients undergoing plastic surgery procedures. In addition, they reported that low serum albumin levels increased the frequency of complications, especially in patients with ulcers (pressure sores, PAD, necrotizing fasciitis, and diabetic ulcers), and they developed more frequent postoperative complications compared to other patients (19). In our study, it is seen that there was a significant relationship between the complication rates and the disease type, just as the correlation between the duration of surgical operation and ASA ps score.…”
Section: Discussionsupporting
confidence: 58%
“…This suggests that increased comorbidities and other issues secondary to senescence might be more responsible for POP. Meanwhile, several authors have reported that age‐related comorbidities and not age itself are risk factors for POP in elderly patients undergoing hip fracture surgery 21,22 . Therefore, advanced age should not be an absolute surgical contraindication 23 …”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, several authors have reported that age-related comorbidities and not age itself are risk factors for POP in elderly patients undergoing hip fracture surgery. 21,22 Therefore, advanced age should not be an absolute surgical contraindication. 23 Reasonable evidence suggested that the male sex was a risk factor for POP in elderly patients with hip fractures.…”
Section: Demographic Variables-related Risk Factorsmentioning
confidence: 99%
“…A multi-center study showed that the risk of postoperative pulmonary complications was higher in patients whose surgery lasted longer than 2 h 13 min. [ 14 ] This is further underlined by a study in patients aged >75 years where a time under anesthesia of >120 min was identified as an independent risk factor for postoperative complications (odds ratio: 6.22) [ 15 ]. Although the VarioGuide procedure significantly reduced the time under anesthesia in our cohort, patient positioning should be further optimized to ensure even less time under anesthesia.…”
Section: Discussionmentioning
confidence: 99%